Resilience in tourism business (a case study of Cherating Lama Village, Pahang) - Nguru, Adamu Ibrahim (2010)
Tourism has proved to be resilient in time of economic crises and shows no sign of slowing down, despite the uncertainty, caused by the events such as September 11, other terrorist threats, and even unexpected new illness like SARS in the beginning of the new century followed by bird flu and recently H1N1 virus (2009). Moreover, uncertainties are large and it may be difficult to reduce them as fast as the system changes. Sustainability involves maintaining the functionality of a system when it is perturbed, or maintaining the elements needed to renew or reorganize if a large perturbation radically alters structure and function. The ability to do this is termed "resilience." In short resilience theory addresses the strengths that people and systems demonstrate that enable them to rise above adversity. This research project therefore, is to provide the reader with an overview in some aspects of resilience theory in relation to a case study in Cherating Lama Village which is known to be one of the famous tourism destination in east cost Malaysia that have undergone the growth, consolidations, stagnation and decline cycle. Without thinking and research, by tourism planners and marketers to know the level of current resilience situation in tourism business and development, the village would be affected both as a tourist destination and in its major role as the income generating source to the local people and the surrounding communities as a whole. Therefore, the research has attempted to find out the chronology of chalets/resorts developments, the measurements or level of resilience and situational analysis of resilience in tourism business in Cherating Lama, with particular emphasis on those that have undergone decline, what make them to decline and what potential resilience methods could be use as a strategy to manage and revitalise/rejuvenate the tourism business in Cherating Lama.